PELAKSANAAN PENGGANTIAN TANAH WAKAFMENURUT HUKUM ADAT ACEH DITINJAU DARI UNDANG – UNDANG NOMOR 41 TAHUN2004 TENTANG WAKAF DAN HUKUM ISLAM (STUDI DI KABUPATEN ACEH BESAR) - RIFQI FATRIZAL (PREMISE LAW JURNAL, 2016)
The result of the research showed that the implementation of the wakaf land compensation at Tanjung Village done by individuals was not in accordance with Law No. 41/2004 on Wakaf because it was not registered and there was no approval from the Agrarian Minister and the Indonesian Wakaf Board. Besides that, the process of transfer was not in accordance with Article 40 F of Law No. 41/2004 on Wakaf because it was not for public interest. According to the Islamic law, land transfer which is not in accordance with its area and price of its original ones was not legally justified by the Islamic law. In consequence, it had no legal certainty; therefore the solution should be based on negotiation stipulated in Article 62, paragraph 1 of Law No. 41/2004 on Wakaf and on the Acehnese customary law, and it should be held at the level of Gampong (village). Keywords: Implementation of Wakaf according to the Acehnese Customary Law, Law No. 41/2004 on Wakaf, the Islamic Law